A transitional wear-resistant coating for electric power connection fittings and preparation method thereof

By applying a transitional wear-resistant coating on the power-connected metal, the problem of insufficient wear-resistant performance in the prior art is solved, higher wear-resistant performance and better interface compatibility are achieved, and the reliability and load-bearing performance of the metal is significantly improved.

CN112080726BActive Publication Date: 2025-04-11CHINA ELECTRIC POWER RESEARCH INSTITUTE CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202010752151.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-07-30
Publication Date
2025-04-11
Estimated Expiration
2040-07-30

AI Technical Summary

Technical Problem

The wear resistance of existing power-connected metal tools is poor, especially in strong wind areas, which can easily lead to surface wear of the metal tools, affecting the load-bearing performance and possibly causing power outages.

Method used

A transition-type wear-resistant coating is adopted. The coating consists of a base layer, a transition layer and a surface layer. The components and thickness of each layer are finely matched to achieve a gradual change in the structure and physical and chemical properties, and reduce the interface stress between the coating and the substrate.

Benefits of technology

It effectively improves the wear resistance of aluminum, copper, magnesium, manganese alloy, reduces the interface stress between the coating and the substrate, improves the bonding strength, and has good interface compatibility between the coating and the substrate, significantly improves the wear resistance and reliability of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112080726B_ABST
    Figure CN112080726B_ABST
Patent Text Reader

Abstract

The present invention provides a transitional wear-resistant coating for power connection fittings and a preparation method thereof, wherein the coating comprises a bottom layer, a transition layer and a top layer; the present invention uses an induction melting method to make a coating target material from blocky simple substances of aluminum, copper, magnesium and manganese, uses a powder metallurgy method to make a coating target material from aluminum oxide and titanium nitride powder, and uses a dual-source synchronous evaporation method to prepare the coating; the present invention not only realizes a gradual change in the organizational structure and physical and chemical properties of the coating, but also improves the wear resistance of the aluminum-copper-magnesium-manganese alloy, enhances the interface compatibility between the coating and the substrate, achieves the effect of avoiding the generation of cracks, and has better adaptability to the operating conditions of overhead power transmission line connection fittings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a wear-resistant coating and a preparation method thereof, and in particular to a transitional wear-resistant coating for electric power connection fittings and a preparation method thereof. Background Art

[0002] Power fittings are metal components that connect and combine various devices in the power system and are used for mechanical transmission, electrical load and device protection. As a type of fittings widely used in overhead transmission lines, connecting fittings should have high mechanical strength, good wear resistance and corrosion resistance to avoid large-scale power outages and other power grid safety accidents caused by fitting damage.

[0003] The materials for the connection fittings in the existing overhead transmission lines are all made of carbon structural steel or alloy structural steel with a tensile strength greater than 375MPa, and some are made of malleable cast iron or ductile iron. Due to the low strength of steel materials, the connection fittings made of steel materials have a large deadweight, and the load-bearing performance requirements of the transmission tower are high, which increases the investment in line construction. In addition, some connection fittings made of carbon structural steel or cast iron have poor wear resistance. When the line passes through a strong wind area, the wind causes severe friction between the fittings, severe wear on the surface of the fittings, and reduced load-bearing performance, which can easily cause disconnection and power outages. Although aluminum alloys such as ZL101, 1050A, and 3A21 are light in weight, compared with steel materials, aluminum alloy materials have poor wear resistance and are not suitable for manufacturing connection fittings. A wear-resistant coating with MoS2, WC, TiN, Al2O3 as main components is prepared on the surface of aluminum alloy materials by electroplating, thermal spraying, laser cladding, physical vapor deposition and other technologies. Although it can improve the wear resistance of the substrate, the coating and the substrate are heterogeneous materials and there is a large interface stress, which is prone to cracking and damage under long-term service conditions. Therefore, it is necessary to provide a coating with excellent wear resistance and good interface compatibility with the substrate. Summary of the invention

[0004] In order to make up for the deficiencies of the prior art, the present invention discloses a transitional wear-resistant coating for power connection fittings and a preparation method thereof. The present invention is implemented by adopting the following technical solutions:

[0005] A transitional wear-resistant coating for power connection hardware, the hardware comprising the following components by mass percentage: Cu 3.2%-5.0%, Mg 1.0%-2.0%, Mn 0.2%-1.2%, and the balance being aluminum; the coating comprising a bottom layer, a transition layer, and a surface layer; the bottom layer has a thickness of 15 μm to 25 μm and comprises the following components by mass percentage: copper 3.42% to 4.41%, magnesium 1.08% to 1.62%, manganese 0.27% to 0.81%, aluminum oxide 10.00%, and the balance being aluminum;

[0006] The transition layer has a thickness of 40 μm to 60 μm and comprises the following components by mass percentage: 2.66% to 3.43% copper, 0.84% ​​to 1.26% magnesium, 0.21% to 0.63% manganese, 15.00% aluminum oxide, 15.00% titanium nitride, and the balance aluminum;

[0007] The surface layer has a thickness of 20 μm to 30 μm and comprises the following components by mass percentage: 1.90% to 2.45% copper, 0.60% to 0.90% magnesium, 0.15% to 0.45% manganese, 20.00% aluminum oxide, 30.00% titanium nitride, and the balance aluminum.

[0008] Furthermore, the thickness of the bottom layer is 16 μm to 20 μm; the thickness of the transition layer is 46 μm to 50 μm; and the thickness of the surface layer is 24 μm to 28 μm.

[0009] The method for preparing any of the above transitional wear-resistant coatings comprises:

[0010] 1) Preparation of aluminum-copper-magnesium-manganese alloy target;

[0011] 2) Preparing aluminum oxide targets and aluminum oxide + titanium nitride targets;

[0012] 3) preparing a bottom coating;

[0013] 4) preparing a transition layer coating;

[0014] 5) Prepare the surface layer coating.

[0015] Further, the step 1) comprises:

[0016] a) Melt aluminum, copper, magnesium and manganese blocks;

[0017] b) refining the molten material obtained in step a) at 800° C. for 3 to 5 minutes;

[0018] c) casting in graphite crucible;

[0019] d) cutting the ingot obtained in step c) into Cylindrical target.

[0020] Furthermore, the step a) includes placing the yttria crucible containing the aluminum, copper, magnesium and manganese in an induction melting device at 0.08-0.1 Pa, and then introducing argon gas to melt the aluminum, copper, magnesium and manganese at a pressure of 0.05 MPa.

[0021] Furthermore, the step 2) comprises: pressing the ball-milled aluminum oxide, aluminum oxide + titanium nitride powder into The material rod is then sintered in a high-temperature furnace at 1500° C. for 10 hours to obtain the alumina and alumina+titanium nitride targets.

[0022] Furthermore, the step 3) includes: using 4 electron guns and 3 water-cooled copper crucibles to synchronously evaporate the aluminum-copper-magnesium-manganese alloy target and the aluminum oxide target, wherein the electron gun beam currents of the aluminum-copper-magnesium-manganese alloy target and the aluminum oxide target are 0.42A-0.51A and 1.14A-1.28A respectively, and the coating deposition time is 20-30min.

[0023] Furthermore, the steps 4) and 5) include: using 4 electron guns and 3 water-cooled copper crucibles to synchronously evaporate the aluminum-copper-magnesium-manganese alloy target and the aluminum oxide + titanium nitride target, wherein the electron gun beam currents of the copper-magnesium-manganese alloy target and the aluminum oxide + titanium nitride target in step 4) are 0.37A~0.45A and 1.39A~1.53A, respectively, and the coating deposition time is 50~70min; the electron gun beam currents of the copper-magnesium-manganese alloy target and the aluminum oxide + titanium nitride target in step 5) are 0.29A~0.38A and 1.65A~1.76A, respectively, and the coating deposition time is 30~40min.

[0024] Furthermore, in the steps 3)-5), the electron gun beam current for heating the hardware substrate is 0.05A-0.09A, the temperature is 400°C±25°C, and the rotation rate of the substrate support is 13r / min.

[0025] Compared with the closest prior art, the technical solution provided by the present invention has the following excellent effects:

[0026] 1) The technical solution provided by the present invention can effectively improve the wear resistance of aluminum-copper-magnesium-manganese alloy, not only realize the lightweight of power connection hardware, but also realize the gradual change of organizational structure and physical and chemical properties, reduce the interface stress between the coating and the substrate, improve the bonding strength between the coating and the substrate, and make the coating and the substrate have good interface compatibility. The wear resistance of the coating is improved by more than 25%, the interface stress between the coating and the substrate is reduced by more than 55%, and the bonding strength between the coating and the substrate is improved by more than 65%.

[0027] 2) The technical solution provided by the present invention is suitable for the design and manufacture of power connection fittings, which can effectively ensure the safe and stable operation of overhead transmission lines in strong wind areas, reduce the operation and maintenance costs of the lines, and improve the service reliability of aluminum-copper-magnesium-manganese alloy. It has better adaptability to the operating conditions of overhead transmission line connection fittings in strong wind areas and has important engineering practical significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of the wear-resistant coating and power connection hardware substrate structure provided by the present invention. DETAILED DESCRIPTION

[0029] In order to better understand the present invention, the content of the present invention is further described below in conjunction with the accompanying drawings of the specification. Unless otherwise specified, the percentages of the various components in the present invention are all mass percentages.

[0030] The invention provides a transitional wear-resistant coating on the surface of an aluminum-copper-magnesium-manganese alloy, which has the following structure: an aluminum-copper-magnesium-manganese alloy substrate, a bottom layer with a thickness of 15 to 25 μm, a transition layer with a thickness of 40 to 60 μm, and a top layer with a thickness of 20 to 30 μm.

[0031] Wherein, the thickness of the bottom layer is preferably 16 μm to 20 μm;

[0032] The thickness of the transition layer is preferably 46 μm to 50 μm;

[0033] The thickness of the top layer is preferably 24 μm to 28 μm.

[0034] Example 1

[0035] The present invention provides a transitional wear-resistant coating on the surface of an aluminum-copper-magnesium-manganese alloy suitable for power connection hardware. By fully considering the matching of various wear-resistant coating components with the aluminum-copper-magnesium-manganese alloy components, an electron beam physical vapor deposition technology is used to prepare the transitional wear-resistant coating on the aluminum-copper-magnesium-manganese alloy substrate. Figure 1 As shown, the coating includes a three-layer wear-resistant coating of a bottom layer, a transition layer, and a surface layer, wherein the bottom layer is a mixture of aluminum-copper-magnesium-manganese alloy and aluminum oxide, and the transition layer and the surface layer are both a mixture of aluminum-copper-magnesium-manganese alloy, aluminum oxide, and titanium nitride. This method achieves a gradual change in the coating structure and physical and chemical properties, which not only effectively improves the wear resistance of the aluminum-copper-magnesium-manganese alloy, but also reduces the interface stress between the coating and the substrate, enhances the interface compatibility between the coating and the substrate, and achieves the effect of avoiding crack generation, which has better adaptability to the operating conditions of overhead transmission line connection fittings.

[0036] The preparation method of the transitional wear-resistant coating on the surface of the aluminum-copper-magnesium-manganese alloy provided in the embodiment is as follows:

[0037] The present invention uses an induction melting method to make aluminum, copper, magnesium and manganese into coating targets, uses a powder metallurgy method to make aluminum oxide and titanium nitride into coating targets, and uses a dual-source synchronous evaporation method to prepare the coating. In order to prevent oxidation of the alloy components, the entire coating preparation process is carried out in a vacuum chamber.

[0038] 1) Preparation of Al-Cu-Mg-Mn alloy target

[0039] After weighing and mixing the bulk single substances of aluminum, copper, magnesium and manganese according to the preset proportion, they are placed in a high-purity alumina crucible and placed in an induction melting device, and evacuated to 0.08Pa-0.1Pa. Argon gas is introduced to make the inner cavity pressure reach 0.05MPa, the power of the equipment is turned on, and the raw materials are melted until they are clear, and refined at 800℃ for 3min-5min. The power of the equipment is cut off, and a high-purity graphite crucible is used for casting to obtain an alloy ingot. Air is filled into the inner cavity of the equipment to break the vacuum state, and the alloy ingot is taken out and processed into a The above steps are repeated to obtain the aluminum-copper-magnesium-manganese alloy target for the bottom layer coating, the aluminum-copper-magnesium-manganese alloy target for the transition layer coating and the aluminum-copper-magnesium-manganese alloy target for the surface layer coating.

[0040] 2) Preparation of matrix samples

[0041] The aluminum-copper-magnesium-manganese alloy ingot is processed into 20×15×3mm by wire cutting method. 3 A rectangular base is cut on each side of the front edge of the base. The circular hole of the substrate was polished with 300#, 500#, and 800# SiC sandpaper to make the surface roughness R a <0.8.

[0042] 3) Preparation of alumina targets and alumina + titanium nitride targets

[0043] Alumina and titanium nitride powders are weighed and mixed according to a preset ratio and placed in a ball mill. Alumina balls and anhydrous ethanol are used as grinding media. In order to ensure sufficient grinding, grinding balls with diameters of 1 mm, 5 mm, and 10 mm are used for mixed ball milling. The mass ratio of powder raw materials, grinding balls, and anhydrous ethanol is about 1:1.5:1.2. The ball mill is placed on a planetary ball mill and mixed for 10 hours. Then the slurry is quickly poured into a tray and dried in a drying oven at 80°C to obtain a uniformly mixed powder. The powder is placed in a stainless steel mold with an inner diameter of 68.5 mm and the powder is pressed into a rod with a molding pressure of 85 kN. The pressed rod is sintered in a high-temperature furnace at 1500°C for 10 hours to obtain The above steps are repeated to obtain the aluminum oxide target for the bottom layer coating, the aluminum oxide + titanium nitride target for the transition layer coating, and the aluminum oxide + titanium nitride target for the surface layer coating.

[0044] 4) Preparation of base coating

[0045] The bottom coating was prepared by electron beam physical vapor deposition equipment, which was equipped with 4 electron guns and 3 water-cooled copper crucibles, and could realize dual-source (aluminum-copper-magnesium-manganese alloy target and alumina target) synchronous evaporation. When preparing the coating, the aluminum-copper-magnesium-manganese alloy target and the alumina target were placed in water-cooled copper crucibles respectively, and the inner cavity of the equipment was evacuated to 10 -3 Pa. The electron gun beam current for evaporating the aluminum-copper-magnesium-manganese alloy target is 0.42A~0.51A, and the electron gun beam current for evaporating the aluminum oxide target is 1.14A~1.28A. By fine-tuning the electron gun beam current, the two targets are ensured to evaporate synchronously in equal proportion to the height. The electron gun beam current for heating the aluminum-copper-magnesium-manganese alloy substrate is 0.05A~0.09A, the substrate temperature is controlled at 400℃±25℃, and the sample holder rotation rate is 13r / min. The coating deposition time is 20min~30min.

[0046] 5) Preparation of transition layer coating

[0047] The transition layer coating was prepared using an electron beam physical vapor deposition device, which was equipped with four electron guns and three water-cooled copper crucibles, and could achieve dual-source (aluminum-copper-magnesium-manganese alloy target and aluminum oxide + titanium nitride target) synchronous evaporation. When preparing the coating, the aluminum-copper-magnesium-manganese alloy target and the aluminum oxide + titanium nitride target were placed in water-cooled copper crucibles respectively, and the inner cavity of the device was evacuated to 10 -3 Pa. The electron gun beam current for evaporating the aluminum-copper-magnesium-manganese alloy target is 0.37A~0.45A, and the electron gun beam current for evaporating the aluminum oxide + titanium nitride target is 1.39A~1.53A. By fine-tuning the electron gun beam current, the two targets are ensured to evaporate synchronously in equal proportion to the height. The electron gun beam current for heating the aluminum-copper-magnesium-manganese alloy substrate is 0.05A~0.09A, the substrate temperature is controlled at 400℃±25℃, and the sample holder rotation rate is 13r / min. The coating deposition time is 50min~70min.

[0048] 6) Preparation of surface coating

[0049] The transition layer coating was prepared by electron beam physical vapor deposition equipment, which was equipped with four electron guns and three water-cooled copper crucibles for synchronous evaporation of dual sources (aluminum-copper-magnesium-manganese alloy target and aluminum oxide+titanium nitride target).

[0050] When preparing the coating, the aluminum-copper-magnesium-manganese alloy target and the aluminum oxide + titanium nitride target were placed in a water-cooled copper crucible with a vacuum degree of 10 -3 Pa vapor deposition equipment. Among them, the electron gun beam current for evaporating aluminum-copper-magnesium-manganese alloy targets is 0.29A-0.38A, and the electron gun beam current for evaporating aluminum oxide + titanium nitride targets is 1.65A-1.76A. By fine-tuning the electron gun beam current, the two targets are evaporated synchronously in equal proportion to the height.

[0051] The electron gun beam current for heating the aluminum-copper-magnesium-manganese alloy substrate is 0.05A-0.09A, the substrate temperature is controlled at 400°C±25°C, the sample holder rotation rate is 13r / min, and the coating deposition time is 30min-40min.

[0052] Example 2-3

[0053] The process step sequence and terminology in Examples 2 and 3 are the same as those in Example 1. The component ratios and performance parameters of Examples 2 and 3 are shown in Table 1:

[0054] Table 1. Ingredient ratio and performance parameters of Examples 2-3

[0055]

[0056] The wear resistance of the transitional wear-resistant coating prepared by the process provided in the embodiment is improved by more than 25%, the interface stress between the coating and the substrate is reduced by more than 55%, and the bonding strength between the coating and the substrate is improved by more than 65%.

[0057] The above are merely embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are included in the scope of the claims of the present invention to be approved.

Claims

1. A transitional wear-resistant coating for power connection fittings, the fittings comprising the following components by mass percentage: Cu 3.2%-5.0%, Mg 1.0%-2.0%, Mn 0.2%-1.2%, and the balance being aluminum, characterized in that: The coating comprises a bottom layer, a transition layer and a surface layer, wherein the bottom layer has a thickness of 15 μm to 25 μm and comprises the following components by mass percentage: 3.42% to 4.41% copper, 1.08% to 1.62% magnesium, 0.27% to 0.81% manganese, 10.00% aluminum oxide, and the balance aluminum; The transition layer has a thickness of 40 μm to 60 μm and includes the following components by mass percentage: 2.66% to 3.43% copper, 0.84% ​​to 1.26% magnesium, 0.21% to 0.63% manganese, 15.00% aluminum oxide, 15.00% titanium nitride, and the balance aluminum; The surface layer has a thickness of 20 μm to 30 μm and comprises the following components by mass percentage: 1.90% to 2.45% copper, 0.60% to 0.90% magnesium, 0.15% to 0.45% manganese, 20.00% aluminum oxide, 30.00% titanium nitride, and the balance aluminum; The preparation method of the transitional wear-resistant coating comprises: 1) Preparation of aluminum-copper-magnesium-manganese alloy targets; 2) Preparation of alumina targets and alumina + titanium nitride targets; 3) preparing the base coating; 4) preparing transition layer coating; 5) preparing surface coating; The step 3) comprises: using 4 electron guns and 3 water-cooled copper crucibles to synchronously evaporate the aluminum-copper-magnesium-manganese alloy target and the aluminum oxide target, wherein the electron gun beam currents of the aluminum-copper-magnesium-manganese alloy target and the aluminum oxide target are 0.42A-0.51A and 1.14A-1.28A respectively, and the coating deposition time is 20-30min; The steps 4) and 5) include: using 4 electron guns and 3 water-cooled copper crucibles to synchronously evaporate the aluminum-copper-magnesium-manganese alloy target and the aluminum oxide + titanium nitride target, wherein the electron gun beam currents of the copper-magnesium-manganese alloy target and the aluminum oxide + titanium nitride target in step 4) are 0.37A-0.45A and 1.39A-1.53A, respectively, and the coating deposition time is 50-70min; the electron gun beam currents of the copper-magnesium-manganese alloy target and the aluminum oxide + titanium nitride target in step 5) are 0.29A-0.38A and 1.65A-1.76A, respectively, and the coating deposition time is 30-40min; In the steps 3) to 5), the electron gun beam current for heating the hardware substrate is 0.05A-0.09A, the temperature is 400°C±25°C, and the rotation rate of the substrate support is 13r / min.

2. The transitional wear-resistant coating according to claim 1, characterized in that: The thickness of the bottom layer is 16 μm to 20 μm; the thickness of the transition layer is 46 μm to 50 μm; and the thickness of the surface layer is 24 μm to 28 μm.

3. The transitional wear-resistant coating according to claim 1, characterized in that: The step 1) comprises: a) Melt aluminum, copper, magnesium and manganese blocks; b) refining the molten material obtained in step a) at 800° C. for 3 to 5 minutes; c) Casting in graphite crucible; d) The ingot obtained in step c) is wire-cut into a cylindrical target of φ68.5 mm.

4. The transitional wear-resistant coating according to claim 3, characterized in that: The step a) comprises placing the yttria crucible containing the aluminum, copper, magnesium and manganese in an induction melting device at 0.08-0.1 Pa, introducing argon gas, and melting the aluminum, copper, magnesium and manganese at a pressure of 0.05 MPa.

5. The transitional wear-resistant coating according to claim 1, characterized in that: The step 2) comprises: pressing the ball-milled aluminum oxide and aluminum oxide + titanium nitride powder into a material rod of φ68.5 mm, and then sintering in a high-temperature furnace at 1500° C. for 10 hours to obtain the aluminum oxide and aluminum oxide + titanium nitride target materials.

Citation Information

Patent Citations

  • Technology method for improving properties of laser-cladding aluminum bronze alloy gradient coating layer

    CN108315734A

  • Anticorrosive and wear-resistant low density composite structure coating on surface of magnesium alloy, and production method thereof

    CN108559987A